(NmEHANIZMY MAGNITOSFERNYH SUBBURX (B/s - (NpONOMAREW(B, (NeWGENIJ aLEKSANDROWI^s; (NgALXPERIN(B, (N`(B.(Ni(B.s; (NsIBIRSKIJ INSTITUT ZEMNOGO MAGNETIZMA(B, (NIONOSFERY I RASPROSTRANENIQ RADIOWOLNs ((NmOSKWA (B:s (NnAUKA(B,s, 1985)
(NbIBLIOGR(B. 172 (NNAZW(B.s
Keywords: (NmAGNITNYE WOZMU]ENIQs; (NgEOFIZIKAs